Improving Campus Alcohol Policies Through Assessment and Scoring. Issue 2 (March 2023) - Jernigan, David H.; Cureg, Janika Blaise; Mitchell, Molly; Arria, Amelia M.
Excessive alcohol consumption is responsible for more than 1, 500 deaths annually among college students, of whom more than one in three report having been drunk during the past 30 days. Campus alcohol policies offer a first line of defense against excessive alcohol use but have received little systematic attention in the research literature. The research team previously developed a taxonomy of campus alcohol policies and sanctions, ranked in order of effectiveness, and assessed the accessibility, clarity, and effectiveness of policies at 15 post-secondary educational institutions. Herein we describe the process of reporting those assessments back to the 15 institutions, providing them with recommendations and technical assistance on how to improve their policies, and then re-assessing school alcohol policies for effectiveness and clarity. Conversations with primary points of contact at each school provided further insight into the process of assessing and improving campus alcohol policies. Of the 15 schools assessed, 11 added more effective policies, and four added more effective consequences during the 2 years following receipt of reports on the assessment. Campuses have control over their own policies, and greater attention to them from researchers and practitioners could better maximize their potential for enhancing student health and safety and supporting student success.